Investigation of the acoustic installation effects of an open-jet anechoic wind tunnel using computational aeroacoustics. (1st December 2020) - Redonnet, S.
Highlights: Acoustic installation effects in a typical open-jet, anechoic wind tunnel are characterized. An advanced CAA (Computational AeroAcoustics) approach is used. Various configurations (from very simple to rather complex) are numerically simulated. Outcomes are both phenomenological (noise physics) and methodological (noise predictions). The study further aids designing and/or conducting better airframe noise experiments. Abstract: This study focuses on acoustic installation effects that may occur during airframe noise experiments conducted in a typical open-jet anechoic wind tunnel, exemplified here by the NASA Langley Quiet Flow Facility (QFF). These acoustic installation effects are assessed through numerical simulation, using Computational Aeroacoustics (CAA). CAA calculations involve either elementary or complex noise sources and account for either canonical or representative steady jet mean flows as well as part, or all, of the testing apparatus. The results highlight how far the refraction/convection effects induced by the open jet flow and/or the reflection/diffraction effects coming from the testing apparatus may impact the acoustic measurements. All this further aids the assessment of acoustic installation effects that might be important in the type of testing typically done in anechoic wind tunnels, such as QFF. This also shows how CAA methods can facilitate the characterization of anechoic facilities, thus offering great potential in the advanced design of optimized aeroacoustic wind tunnels.